Modular horizontal network within mouse primary visual cortex - Burkhalter, Andreas; Ji, Weiqing; Meier, Andrew M.; D’Souza, Rinaldo D. (Frontiers in Neuroanatomy, 2024)
Interactions between feedback connections from higher cortical areas and local horizontal connections within primary visual cortex (V1) were shown to play a role in contextual processing in different behavioral states. Layer 1 (L1) is an important part of the underlying network. This cell-sparse layer is a target of feedback and local inputs, and nexus for contacts onto apical dendrites of projection neurons in the layers below. Importantly, L1 is a site for coupling inputs from the outside world with internal information. To determine whether all of these circuit elements overlap in L1, we labeled the horizontal network within mouse V1 with anterograde and retrograde viral tracers. We found two types of local horizontal connections: short ones that were tangentially limited to the representation of the point image, and long ones which reached beyond the receptive field center deep into its surround. The long connections were patchy and terminated preferentially in M2 muscarinic acetylcholine receptor-negative (M2-) interpatches. Anterogradely labeled inputs overlapped in M2-interpatches with apical dendrites of retrogradely labeled L2/3 and L5 cells, forming module-selective loops between topographically distant locations. Previous work showed that L1 of M2-interpatches receive inputs from the lateral posterior thalamic nucleus (LP) (D'Souza et al., 2019) and from a feedback network from areas of the medial dorsal stream, including the secondary motor cortex (Meier et al., 2024). Together these findings suggest that interactions in M2-interpatches play a role in processing visual inputs produced by object-and self-motion.